Primary Total Laryngectomy versus Organ Preservation for Locally Advanced T3/T4a Laryngeal Cancer. (26th June 2022) - Lee, Maxwell Y.; Belfiglio, Mario; Zeng, Johnathan; Fleming, Christopher W.; Koyfman, Shlomo; Joshi, Nikhil P.; Lamarre, Eric; Prendes, Brandon; Scharpf, Joseph; Lorenz, Robert R.; Woody, Neil M.; Adelstein, David J.; et al.
Abstract : Objective: Organ preservation (OP) treatment for advanced laryngeal cancer has increased compared to primary total laryngectomy. Our study compares oncologic and functional outcomes between these approaches. Study Design: Retrospective cohort study. Setting: Single tertiary care institution. Methods: Retrospective review of patients receiving primary total laryngectomy or OP for laryngeal cancer between 1/1/2000 and 12/31/2018. Results: A total of 118 patients received primary total laryngectomy and 119 received OP. Overall survival was similar between total laryngectomy and OP. When stratified by T stage, disease‐free survival was worse among T3 patients receiving OP versus total laryngectomy. In T3 patients, 28 OP patients experienced local recurrence (28.9%) compared to 3 total laryngectomy patients (7.1%; p < 0.01). In total, 20 OP patients with local recurrence received salvage surgery. These patients had similar overall survival to patients who underwent initial total laryngectomy (TL). About 14 OP patients with local recurrence did not receive salvage surgery. About 89 (75.4%) TL patients achieved normal diet as compared to 64 (53.8%) OP patients ( p < 0.001). In TL patients, 106 (89.8%) received primary or secondary tracheoesophageal‐prosthesis, 82 (77.4%) of whom achieved completely understandable speech. Conclusions: There was no difference in survival by treatment in T4 patients, possibly because of strict patient selection. However, disease‐free survival was worse in T3 patients receiving OP, likely due to a high local recurrence rate. Approximately 40% of patients with local recurrence were not eligible for salvage laryngectomy. TL patients had comparable swallowing and speech outcomes with OP patients. Level of Evidence: 3 Laryngoscope, 133:1122–1131, 2023 Abstract : Disease free survival in patients with T3 laryngeal cancer was worse in patients receiving organ preservation compared to total laryngectomy, likely due to a high local recurrence rate. 40% of patients with local recurrence were not eligible for salvage laryngectomy, contributing to a trend towards worse survival with organ preservation.